Study the Infrared spectroscopy of the Fe2O3 and MgO oxides - Huthama Abd Mohammad Sulayman (College of Education for Pure Sciences, 2013)
Abstract The Infrared spectroscopy in the frequency range (400 cm-1) to (1000 cm-1) of (MgO)x(Fe2O3)1-x compounds at room temperature have been investigated. These compounds result from the solid state reaction of the Fe2O3 and MgO oxides at high temperatures around (1000 Co). The infrared spectrum of these compounds show two main absorption bands; the first band, ν1 is caused by the stretching vibrations at the tetrahedral sites and the second band, ν2 is caused by the stretching vibrations at the octahedral sites of the lattice structure. Values of ν1 are higher than ν2. Moreover, the force constants of the bonds at the tetrahedral sites, Ftet and octahedral sites, Foct have also been calculated. Values of Ftet are higher than those of Foct. The results of this study agree quite well with the related studies for these compounds